Optimization of Aqua Gallon Water Distribution Cost at Mega Mas Water Depot by VAM and MODI - Fatikasari, Najma; Yasinta, Bhernita Mila; Albar, Wakhid Fitri (Universitas Negeri Padang, 2023)
This study aims to obtain optimal distribution costs for selling gallons of water at the Air Mega Mas Depot, Sekaran. The data analysis method used is the transportation method, using the VAM (Vogel's Approximation Method) method for the initial solution and the optimal test using the MODI (Modified Distribution) method. Air Mega Mas Depot is faced with the problem of increasing marketing costs due to the lack of regular distribution patterns from the source to the marketing destination, so the company tries to optimize the transportation costs incurred. The distribution of gallon water products at the Air Mega Mas Depot using the transportation method gets optimal results. The costs incurred by the Air Mega Mas Depot for the distribution of gallons of water for a 2-month period (March-April) are Rp. 2.520.000 while for the optimal calculation results for the distribution of gallons of water, a cost of IDR 2.435.000 is obtained. Based on this analysis, Air Mega Mas Depot can optimize distribution costs for the March-April period of IDR 85.000.